Penerapan Project Based Learning dengan Pendekatan Kontekstual untuk Meningkatkan Hasil Belajar Prakarya dan Kewirausahaan - Novita Erliana Sari; Yahya Reka Wirawan; Reza Krisyulimda; Endang Sri Maruti; Badrus Sholeh (Journal on Education, 2023)
This research was conducted to find out the application of project based learning learning models with a contextual approach to product promotion media material for Class XI SMA Negeri 1 Babadan. This type of research is Classroom Action Research (PTK) class observation research with 2 cycles, where each cycle has 4 stages (1) planning, (2) implementation, (3) observation, (4) reflection. Data collection is done through observation, tests and documentation. In cycle 1, 14 students achieved the KKM while the other 11 students had not been able to reach the KKM. The highest score obtained was 83 while the lowest score was 52. The percentage of students who achieved KKm was 56%. While those who have not reached the KKM is 44%. In cycle 2 the number of students who achieved the KKM was 21 students (83%). While students who have not reached the KKM are 4 students or 17%. For this reason, it was concluded that there was an increase in student learning outcomes by 27%. Thus it can be said that the application of a project-based learning model with a contextual approach to craft and entrepreneurship subjects has succeeded in achieving the desired goals in learning.